PENERAPAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) MENGGUNAKAN HPY DALAM DIVISI KEUANGAN PADA PT. X - Ningrum, Lutfi Cahya; Warmana, G. Oka (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Advancements in information technology have prompted compasnies to adopt information systems that can enhance operation efficiency and accuracy. A widely implemented solution is the Enterprise Resource Planning (ERP) system, this study investigates the implementation of HPY-based ERP within the finance division of PT. X, focusing on improving operational efficiency and the quality and accuracy of the generated data. The research employed a descriptive qualitative approach, collecting data through semi-structured interviews with finance division employees directly involved in using the ERP system. The findings indicate that the HPY ERP implementation successfully integrated financial processes, accelerated reporting cycles, and reduced recording errors. The system’s implementation also fostered improved cross-departmental collaboration and supported real-time data driven decision-making. Despite existing challenges, such as system errors and input data miscommunication, training and procedural adjustments have been implemented to address them. Overall, the HPY ERP has proven to enhance the efficiency and quality of financial data management at PT. X, establishing crucial foundation for more structured and digital business growth